2018
DOI: 10.1155/2018/8587475
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Induced DNA Damage Associates with Abundance of Mitochondrial DNA in White Blood Cells of the Untreated Schizophrenic Patients

Abstract: Objective The aim of this study was (1) to examine the leukocyte mtDNA copy number (CN) in unmedicated (SZ (m−)) and medicated (SZ (m+)) male patients with paranoid schizophrenia (SZ) in comparison with the healthy male controls (HC) and (2) to compare the leukocyte mtDNA CN with the content of an oxidation marker 8-oxodG in lymphocytes of the SZ (m−) patients. Methods We evaluated leukocyte mtDNA CN of 110 subjects with SZ in comparison with 60 male HC by the method qPCR (ratio mtDNA/nDNA (gene B2M) was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
(45 reference statements)
1
20
0
1
Order By: Relevance
“…In the present study we showed, with this specific concentration, that the copy-number of mtDNA increased significantly after 24-h treatment (data not shown), a sensitive index indicating cellular oxidative stress, inflammation and mitochondrial dysfunction [50,51]. Our result is in accordance with previous work showing an association between an altered mtDNA copy-number and cellular stress/schizophrenia pathology [52][53][54]. We found that treatment for 24 h significantly increased the copy number of mtDNA.…”
Section: Clozapine Counteracts Ketamine-induced Decrease In Nsc Viabisupporting
confidence: 92%
“…In the present study we showed, with this specific concentration, that the copy-number of mtDNA increased significantly after 24-h treatment (data not shown), a sensitive index indicating cellular oxidative stress, inflammation and mitochondrial dysfunction [50,51]. Our result is in accordance with previous work showing an association between an altered mtDNA copy-number and cellular stress/schizophrenia pathology [52][53][54]. We found that treatment for 24 h significantly increased the copy number of mtDNA.…”
Section: Clozapine Counteracts Ketamine-induced Decrease In Nsc Viabisupporting
confidence: 92%
“…For example, the cells of the unmedicated SZ patient as well as the cells exposed to IR increase the mtDNA amount (Chestkov et al, 2018b). The level of the lymphocyte DNA damage in SZ patients is comparable with the DNA damage of the nuclear workers.…”
Section: Introductionmentioning
confidence: 87%
“…TR-rDNA analysis by qPCR method and primers for mtDNA and TR-rDNA are described earlier (44, 46). 8-oxoguanine DNA glycosylase (fpg) were used for gDNA hydrolysis under manufacturer's protocol (Merck).…”
Section: Methodsmentioning
confidence: 99%